Higher Dimensional Bianchi Type-I Cosmological Models With Massive String in General Relativity - Singh, Kangujam Priyokumar; Baro, Jiten; Meitei, Asem Jotin (Frontiers in Astronomy and Space Sciences, 2021)
Here we studied Bianchi type-I cosmological models with massive strings in general relativity in five dimensional space time. Out of the two different cases obtained here, one case leads to a five dimensional Bianchi type -I string cosmological model in general relativity while the other yields the vacuum universe in general relativity in five dimensional space time. The physical and geometrical properties of the model universe are studied comparing with the present day's observational findings. It is observed that our model is anisotropic, expanding, shearing, decelerate at early stage and then accelerate in late time universe. The model expands along x, y and z axes and the extra dimension contracts and becomes unobservable at $t→∞$. We also observed that the sum of the energy density $(ρ)$ and the string tension density $(λ)$ vanishes$(ρ+λ=0)$.